Perlindungan Hukum terhadap Pengikut Aliran Syiah di Kabupaten Sampang Jawa Timur - Maududi, Achmad (Al-Daulah: Jurnal Hukum dan Perundangan Islam, 2014)
Abstract : The followers of Syiah religious sect in Sampang can get legal protection when they want to do Baiat again to the teachings of Ahlus sunnah wal Jamaah. It is agreed, because they believe Itsna Asyarah Syiah religious sect that its existing banned in Indonesia. Legal protection for them is the right of citizens of Indonesia stipulated in the 1945 constitution. The guarantee of 1945 constitution, written constitution, in the case of citizens protection states itself as the law state that the implementation of its goverment based on law. As a consequence of the law state, recognation, respect, and protection of human rights should get a serious attention without discrimination in any forms. That the violence for whatever reason that may lead to violence action on the protect of religion is not justified forever. This is in accordance with embodiments of article 28 and 29 of 1945 constitution which says that every citizens has the right to run their each religious beliefs and convictions. Keywords: Legal protection, Syiah, Sampang